Laparoscopy and chronic pelvic pain - Del Castillo, Angélica (2015)
A study of 96 patients undergoing gynecological laparoscopy Clinic and Hospital San Pablo Vitarte, EsSalud in Lima, Peru, for chronic pelvic pain who do not respond to medical treatment is presented, evaluating the effectiveness of this methodology, which demonstrates its acceptability and reliability.